Zapisz w jak najprostszej postaci:
2(7x+5)-6(x-2)

5(3-2x)-(4x+6)*3

12x+16 10x+15
--------- - -----------
4 5


9-6x 21-14x
--------- - -----------
3 7




Oblicz wartości liczbowe wyrażeń:


3(x2-2x+3)-2(x2-5x-1) dla x=2
a(2ab+b) - b (a-2ab +a2) dla a=0,1 i b= -10

2

Odpowiedzi

2010-03-04T18:50:29+01:00
3(2.2-2.2+3)-2(2.2-5.2-1)=3(4-4+3)-2(4-10-1)=3.3-2.(-7)=6+14=20
te kropki to mnożenie
2010-03-04T18:53:35+01:00
2(7x+5)-6(x-2)=(14x+10)-(6x-12)=14x+10-6x+12=8x+22
5(3-2x)-(4x+6)*3=15-10x-(12x+18)=15-10x-12x-18=-3-22x


3(x2-2x+3)-2(x2-5x-1) dla x=2
3(2*2-2*2+3)-2(2*2-5*2-1)=3*3-(2*(-7))=9+14=23

a(2ab+b) - b (a-2ab +a2) dla a=0,1 i b= -10
0,1(2*0,1*(-10)) +10(0,1-2*0,1*(-10)+0,1*2)=0,1*(-2) + 10*2,3= -0,2 + 23=22,8
1 5 1